Photophysical and Solvatochromic Studies of 4-(methylthio)-2-oxo-6-phenyl-2H-pyran-3-carbonitrile Derivatives (International Journal of Scientific Research in Science and Technology, 2024)
Herein we report a photophysical and solvatochromic study of (4-(methylthio)-2-oxo-6-phenyl-2H-pyran-3-carbonitrile derivatives. Photophysical properties of synthesized compounds were investigated in different solvents of varying polarity. It was found that for all studied compounds no distinguishable behaviour was observed for absorption in different solvents whereas some notable changes were observed in emission spectra. Solvent dependent spectral properties of compounds were investigated using Lippert- Mataga plot and empirical solvent parameter ET(30).